Lithium secondary battery negative electrode comprising pattern and lithium secondary battery comprising negative electrode
By introducing patterns into the negative electrode active material layer of lithium secondary battery, volume expansion is controlled, and the problem of volume expansion of silicon-based active materials causing disconnection of conductive paths during charging and discharging is solved, and high-life characteristics and fast charging performance are achieved. Lithium secondary battery.
Patent Information
- Application Number
- CN202380049998.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-15
- Filing Date
- 2023-12-14
- Publication Date
- 2025-02-18
AI Technical Summary
When existing lithium secondary batteries use silicon-based active materials as negative electrode materials, volume expansion during charging and discharging leads to disconnection of conductive paths, reducing battery performance, and limited control over the content of conductive materials and adhesives.
The pattern is introduced into the negative electrode active material layer of the lithium secondary battery to ensure that the volume of the pattern part accounts for between 5% and 30% of the total volume, and the volume expansion is controlled by adjusting the physical volume relationship.
By reducing volume swelling during charging and discharging, the life characteristics of lithium secondary batteries are maximized, and high density, high capacity characteristics and excellent fast charging performance are provided.
Smart Images

Figure CN119487645A_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0175723 filed in the Korean Intellectual Property Office on December 15, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode for a lithium secondary battery including a pattern and a lithium secondary battery including the negative electrode. Background Art
[0003] As a part of the increasing demand for the use of alternative or clean energy due to the rapid increase in the use of fossil fuels, the most active research field is the field of power generation and storage using electrochemical reactions.
[0004] Currently, secondary batteries are a representative example of electrochemical devices using this type of electrochemical energy, and their use tends to be increasingly widespread.
[0005] With the technological development and increasing demand of mobile devices, the demand for secondary batteries as energy sources has increased dramatically. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, the manufacturing method of high-density electrodes with higher energy density per unit volume as electrodes of such high-capacity lithium secondary batteries is being actively studied.
[0006] Generally, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and silicon-based particles having a high discharge capacity can be used as the negative electrode active material.
[0007] In particular, in accordance with the demand for high-density energy batteries in recent years, a method of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times higher than that of graphite-based materials, as negative electrode active materials is being actively studied. However, silicon-based compounds, which are high-capacity materials, have a large capacity compared to commonly used graphite, but their volume rapidly expands during charging, thereby disconnecting the conductive path and degrading battery characteristics.
[0008] Therefore, in order to solve the problems that arise when using silicon-based compounds as negative electrode active materials, methods of suppressing volume expansion itself, such as methods of controlling driving potential, methods of additionally coating a thin film on an active material layer, and methods of controlling the particle size of silicon-based compounds, or various measures to prevent disconnection of conductive paths have been discussed. However, the above methods may instead deteriorate battery performance, and therefore, their application is limited, and thus there is still a limitation in the commercialization of the manufacture of batteries including negative electrodes having a high content of silicon-based compounds.
[0009] In other words, in order to maximize the capacity characteristics and meet the fast charging performance, a negative electrode using a silicon-based active material must be applied, but no method has been found to solve the problem caused by the volume expansion of the above-mentioned silicon-based active material itself. In particular, research is being conducted to control the volume expansion of the negative electrode by using a conductive material and a binder together, and the negative electrode must contain a high content of silicon-based active materials. However, since the content of conductive materials and binders is less than that of active materials, the control of their content is very limited. That is, there are many restrictions on changing the composition and content.
[0010] Therefore, in order to improve capacity performance, research is required to suppress volume expansion of silicon-based active materials due to insertion and extraction of lithium during charge and discharge, even when the silicon-based active materials are used as negative electrode active materials.
[0011] Prior art literature
[0012] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention
[0013] Technical issues
[0014] Research is being conducted to control the volume expansion of the negative electrode, which must contain a high content of silicon-based active materials, by using a conductive material and a binder together. However, since the content of the conductive material and the binder is small compared to the active material, the control of their content is very limited. That is, there are many restrictions on changing the composition and content.
[0015] In view of this, it has been found through studies that when a pattern is introduced into the negative electrode active material layer of a negative electrode including a silicon-based active material, and the pattern satisfies a specific volume, the above-mentioned problem can be solved.
[0016] Therefore, the present application relates to a negative electrode for a lithium secondary battery including a pattern capable of solving the above-mentioned problems and a lithium secondary battery including the negative electrode.
[0017] Technical Solution
[0018] An exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a negative electrode collector layer; and a negative electrode active material layer, the negative electrode active material layer being formed on one surface or both surfaces of the negative electrode collector layer, wherein the negative electrode active material layer comprises a pattern portion and satisfies the following Formula 1:
[0019] [Formula 1]
[0020] 5 ≤ [B / (A+B)] × 100(%) ≤ 30
[0021] In the above formula 1,
[0022] A refers to the volume of the negative electrode active material layer excluding the pattern portion, and
[0023] B refers to the volume of the pattern portion of the negative electrode active material layer.
[0024] An exemplary embodiment of the present application provides a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
[0025] Beneficial Effects
[0026] The negative electrode for the lithium secondary battery of the present invention comprises a silicon-based active material, and its goal is high capacity and high energy density. In this case, the silicon-based active material is high in the negative electrode active material layer, and therefore, volume expansion during charge and discharge may cause problems. In the case of the negative electrode for the lithium secondary battery according to the present application, the negative electrode active material layer comprises a pattern portion, and in particular, the volume of the pattern portion and the negative electrode active material layer satisfies the relationship of the above formula 1.
[0027] That is, the volume expansion problem is solved by adjusting the physical volume relationship while maintaining the composition, rather than by adjusting the composition of the negative electrode active material layer. When the silicon-based negative electrode is finally used, in order to satisfy the range (less than 5% to 10%) in which the volume expansion rate of the negative electrode active material layer does not become a use problem, the volume of the pattern portion is set accordingly, and the volume ratio is adjusted to the range of the above formula 1.
[0028] Therefore, the negative electrode including the negative electrode active material layer satisfying the above formula 1 can maximize the life characteristics of the lithium secondary battery by reducing the volume expansion during the charge and discharge process, and can provide a lithium secondary battery having the advantages of a silicon-based negative electrode, namely high density and high capacity characteristics, while having excellent fast charging performance.
[0029] The above configuration has a favorable effect not only on stacked pouch cells but also on cylindrical and square cells rolled into a roll, and under the above configuration, there is no difference in volume expansion even when the formation charging speed is increased compared to the existing conditions. In addition, it is characterized in that not only the expansion in the x and y directions but also the thickness change in the z direction is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a diagram showing a stack structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0031] Figure 2is a diagram illustrating a stack structure of a lithium secondary battery according to an exemplary embodiment of the present application.
[0032] Figure 3 is a diagram showing a structure in which an active material layer of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application is patterned.
[0033] <Description of symbols>
[0034] 10: Negative electrode collector layer
[0035] 20: Negative electrode active material layer
[0036] 30: Diaphragm
[0037] 40: Positive electrode active material layer
[0038] 50: Positive electrode collector layer
[0039] 60: Pattern part
[0040] 100: Negative electrode for lithium secondary battery
[0041] 200: Positive electrode for lithium secondary battery DETAILED DESCRIPTION
[0042] Before describing the present invention, some terms are first defined.
[0043] In the present specification, when a component “includes,” “contains,” or “has” a constituent element, unless otherwise specifically described, this does not mean that other constituent elements are excluded but means that other constituent elements may further be included.
[0044] In the present specification, 'p to q' means a range of 'p or more and q or less'.
[0045] In the present specification, the "specific surface area" is measured by the BET method, specifically, calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) by using BELSORP-mini II available from BEL Japan, Inc. That is, in the present application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.
[0046] In this specification, "Dn" refers to particle size distribution, and refers to the particle size at n% point in the cumulative distribution of the number of particles according to the particle size. That is, D50 is the particle size (average particle size) at 50% point in the cumulative distribution of the number of particles according to the particle size, D90 is the particle size at 90% point in the cumulative distribution of the number of particles according to the particle size, and D10 is the particle size at 10% point in the cumulative distribution of the number of particles according to the particle size. On the other hand, the average particle size can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), wherein the difference in diffraction patterns according to particle size is measured when the laser beam passes through the particles, and then the particle size distribution is calculated.
[0047] In an exemplary embodiment of the present application, the particle size or particle diameter may refer to an average diameter or a representative diameter of individual crystal grains constituting the metal powder.
[0048] In the present specification, the description "a polymer includes a certain monomer as a monomer unit" means that the monomer participates in a polymerization reaction and is included in the polymer as a repeating unit. In the present specification, when a polymer includes a monomer, this should be interpreted as the same as the polymer including the monomer as a monomer unit.
[0049] In this specification, it is to be understood that the term 'polymer' is used in a broad sense and includes copolymers unless otherwise specified as 'homopolymer'.
[0050] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene conversion molecular weights measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specifically described, molecular weight refers to weight average molecular weight.
[0051] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.
[0052] An exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a negative electrode collector layer; and a negative electrode active material layer, the negative electrode active material layer being formed on one surface or both surfaces of the negative electrode collector layer, wherein the negative electrode active material layer comprises a pattern portion and satisfies the following Formula 1:
[0053] [Formula 1]
[0054] 5 ≤ [B / (A+B)] × 100(%) ≤ 30
[0055] In the above formula 1,
[0056] A refers to the volume of the negative electrode active material layer excluding the pattern portion, and
[0057] B refers to the volume of the pattern portion of the negative electrode active material layer.
[0058] Figure 3 : is a diagram showing a structure in which an active material of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application is patterned. Specifically, A refers to the volume of the negative electrode active material layer excluding the pattern portion, and B refers to the volume of the pattern portion in the negative electrode active material layer.
[0059] In the present application, the pattern portion may be defined as an uncoated region of the negative electrode active material layer where the negative electrode active material layer is not disposed. That is, the pattern portion is a portion of the negative electrode current collector layer where the negative electrode active material layer is not disposed, and is different from a structure in which the negative electrode active material layer has a pattern shape by being separated by a partition wall or other materials.
[0060] According to the present invention, the negative electrode comprising a negative electrode active material layer satisfying the above formula 1 can maximize the life characteristics of the lithium secondary battery by reducing the volume expansion during the charge and discharge process, and can provide a lithium secondary battery having the advantages of a silicon-based negative electrode, namely high density and high capacity characteristics, and excellent fast charging performance. The pattern portion of the present invention can only play the above role when the negative electrode active material layer is not formed. If a partition wall is formed for demarcation, unlike the pattern portion of the present invention, the portion blocked by the partition wall cannot accommodate volume expansion, and therefore the effect of alleviating volume expansion cannot be obtained.
[0061] In an exemplary embodiment of the present application, the above Formula 1 may satisfy the range of 5≤[B / (A+B)]×100(%)≤30, specifically, 6≤[B / (A+B)]×100(%)≤25, more specifically, 10≤[B / (A+B)]×100(%)≤25.
[0062] The present application solves the volume expansion problem by adjusting the physical volume relationship while maintaining the composition, rather than by adjusting the composition of the negative electrode active material layer. When a silicon-based negative electrode is finally used, in order to satisfy the range (less than 5% to 10%) in which the volume expansion rate of the negative electrode active material layer does not become a use problem, the volume of the pattern portion is set accordingly, and the volume ratio is adjusted to the range of the above formula 1.
[0063] When the range of the above formula 1 is satisfied, not only the volume expansion in the stacked pouch battery but also the volume expansion in the cylindrical and square batteries rolled into a roll can be controlled, thereby producing a favorable effect. In addition, even when the formation charging speed is increased compared to the existing conditions, there is no difference in volume expansion, and not only the expansion in the x and y directions can be reduced, but also the thickness change in the z direction can be reduced.
[0064] In an exemplary embodiment of the present application, the above Formula 1 means a ratio of the volume of the pattern portion to the total volume of the negative electrode active material layer, and the unit of Formula 1 may be expressed as %.
[0065] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the negative electrode active material layer satisfies the following Formula 2:
[0066] [Formula 2]
[0067] [{(x+x1)(y+y1)(z+z1)-xyz} / xyz ] × 100(%) < 50%
[0068] In the above formula 2,
[0069] x, y, and z are respectively the total width, total length, and total thickness of the negative electrode active material layer including the pattern after manufacturing the negative electrode for a lithium secondary battery, and
[0070] x1, y1, and z1 are the length changes in the x, y, and z directions, respectively, immediately after charging to 4.2 V (0.05C cutoff) with 1 / 3C CC-CV and then discharging to 2.5 V with 1 / 3C CC after fabricating the negative electrode for a lithium secondary battery.
[0071] The above formula 2 can satisfy [Formula 2]<50%, specifically, [Formula 2]<48%, or [Formula 2]<45%, and 5%<[Formula 2], 10%<[Formula 2], 15%<[Formula 2], 20%<[Formula 2] or 25%<[Formula 2].
[0072] That is, the above formula 2 may mean the volume expansion rate of the entire volume of the negative electrode active material layer after the lithium secondary battery is subjected to an activation process in a new state (i.e., single charge to 4.2 V (0.05 C cutoff) at 1 / 3C CC-CV and then discharged to 2.5 V at 1 / 3C CC). Since the negative electrode active material layer includes a pattern portion satisfying the range of the above formula 1, it can satisfy the range of the above formula 2.
[0073] Specifically, the above formula 2 can be Figure 3is confirmed in the above. x is the length in the TD direction, which means the total width of the negative electrode active material layer; y is the length in the MD direction, which means the total length of the negative electrode active material layer; and z is the thickness of the negative electrode active material layer. In this case, x1, y1, and z1 respectively refer to the length changes in the x, y, and z directions after the negative electrode for lithium secondary batteries is manufactured and after the above activation process is performed.
[0074] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the negative electrode active material layer satisfies the following Formula 3:
[0075] [Formula 3]
[0076] [{(x+x2)(y+y2)(z+z2)-xyz} / xyz] × 100(%) < 100%
[0077] In the above formula 3,
[0078] x, y, and z are respectively the total width, total length, and total thickness of the negative electrode active material layer including the pattern after manufacturing the negative electrode for a lithium secondary battery, and
[0079] x2, y2, and z2 refer to the length changes in the x, y, and z directions, respectively, after 300 cycles of charging at 1 C CC-CV to 4.2 V (0.05 C cutoff) and discharging at 0.5 C CC to 3.0 V after fabricating a negative electrode for a lithium secondary battery.
[0080] The above formula 3 may satisfy [formula 3]<100%, specifically, [formula 3]<97% or [formula 3]<95%, and 50%<[formula 3], 55%<[formula 3] or 60%<[formula 3].
[0081] That is, the above formula 3 may mean the volume expansion rate of the entire volume of the negative electrode active material layer after the lithium secondary battery undergoes 300 cycles in a new state (i.e., 300 cycles of charging to 4.2 V (0.05 C cutoff) at 1C CC-CV and then discharging to 3.0 V at 0.5 C CC). Since the negative electrode active material layer includes a pattern portion satisfying the range of the above formula 1, it can satisfy the range of the above formula 3.
[0082] Specifically, the above formula 3 can be Figure 3 It is confirmed in the above. x is the length in the TD direction, which means the total width of the negative electrode active material layer; y is the length in the MD direction, which means the total length of the negative electrode active material layer; and z is the thickness of the negative electrode active material layer. In this case, x2, y2, and z2 respectively refer to the length changes in the x, y, and z directions after the negative electrode for lithium secondary battery is manufactured and then subjected to the above 300 cycles.
[0083] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the negative electrode active material layer satisfies the following Formula 4:
[0084] [Formula 4]
[0085] 5 ≤ xyz - {(xi × n)yz + x(yj × m)z - nmxiyjz} ≤ 30
[0086] In the above formula 4,
[0087] x, y, and z are respectively the total width, total length, and total thickness of the negative electrode active material layer including the pattern after manufacturing the negative electrode for a lithium secondary battery, and
[0088] n is the number of patterns in the x direction,
[0089] m is the number of patterns in the y direction,
[0090] xi refers to the width of the pattern,
[0091] yj refers to the length of the pattern,
[0092] i is an integer in the range of 1 to n, and
[0093] j is an integer in the range of 1 to m.
[0094] Figure 3 Corresponding to the case where the pattern portion is formed as a 2D pattern. In this case, n is the number of patterns in the x direction. When n is 3, i can be expressed as an integer in the range of 1 to 3, and x1, x2, and x3 can refer to the width of each pattern. Similarly, m is the number of patterns in the y direction. When m is 3, j is an integer in the range of 1 to 3, and y1, y2, and y3 can refer to the length of each pattern.
[0095] The above formula 4 may mean a volume based on the total volume of the negative electrode active material layer, excluding the volume of the pattern portion included in the negative electrode active material layer, and may mean an actual volume included in the negative electrode active material layer. That is, if the above formula 4 is less than the above range, the capacity characteristics cannot be ensured, and if the above formula 4 exceeds the above range, the volume expansion is not controlled, and the life characteristics are reduced instead.
[0096] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the pattern portion includes one or more selected from the group consisting of a 1D pattern, a 2D pattern, a V-shaped pattern, and a U-shaped pattern.
[0097] In this case, the 1D pattern may mean a pattern formed only in the length direction or the width direction in the negative electrode active material layer, and the 2D pattern may mean a pattern formed in both the length direction and the width direction in the negative electrode active material layer. In addition, a V-shaped or U-shaped pattern may mean that the shape of the formed pattern is V-shaped or U-shaped.
[0098] In the present application, a negative electrode for a lithium secondary battery is provided, wherein the negative electrode active material layer contains a negative electrode active material layer composition, and the negative electrode active material layer composition contains a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.
[0099] In this case, the silicon-based active material can be used as the negative electrode active material.
[0100] The negative electrode active material layer composition according to an exemplary embodiment of the present invention solves the problems in the related art by using the negative electrode active material layer having the above-mentioned pattern portion even when using a silicon-based active material.
[0101] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloy.
[0102] The active material of the present invention contains a silicon-based active material. The silicon-based active material may be SiOx, Si / C, or Si. SiOx may include a compound represented by SiOx (0 ≤ x < 2). Since SiO2 does not react with lithium ions and cannot store lithium, x is preferably within the above range. The silicon-based active material may be Si / C or Si composed of a composite of Si and C. In addition, two or more of the above silicon-based active materials may be used in combination. The negative electrode active material may also contain a carbon-based active material together with the above silicon-based active material. The carbon-based active material can contribute to improving the cycle characteristics or battery life performance of the negative electrode or secondary battery of the present invention.
[0103] Generally, it is known that the capacity of the silicon-based active material is 10 times higher than that of the carbon-based active material. Therefore, when the silicon-based active material is applied to the negative electrode, it is expected that an electrode with a high level of energy density can be achieved even with a thin thickness.
[0104] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more.
[0105] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) contained in the silicon-based active material may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0106] Based on 100 parts by weight of the silicon-based active material, the silicon-based active material according to the present application may contain 70 parts by weight or more of SiOx (x = 0). When compared with a silicon-based active material using a SiOx (0 < x < 2)-based active material as the main material, its theoretical capacity is much lower than that of the silicon-based active material of the present application. That is, if a SiOx (0 < x < 2)-based active material is used, it is impossible to achieve conditions equivalent to the charge and discharge capacity of the silicon-based active material of the present invention even if the active material itself is processed in any way.
[0107] In an exemplary embodiment of the present application, pure silicon (Si) may be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, based on 100 parts by weight of the total silicon-based active material as described above, pure Si particles (SiOx (x = 0)) not combined with other particles or elements within the above range are included.
[0108] The capacity of the silicon-based active material is significantly higher than that of the commonly used graphite-based active material, so there have been many attempts to apply it. However, the volume expansion rate of the silicon-based active material during the charge and discharge process is high, so only a small amount of the silicon-based active material is mixed with the graphite-based active material for use.
[0109] Therefore, in the present invention, while using the silicon-based active material as the negative electrode active material to improve the capacity performance, in order to solve the problems of maintaining the conduction path and the combination of the conductive material, binder, and active material caused by the above volume expansion, a negative electrode including a pattern portion satisfying the above formula 1 is manufactured.
[0110] Note that the average particle size (D50) of the silicon-based active material of the present invention can be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is within the above range, the specific surface area of the particles is within a suitable range, so that the viscosity of the negative electrode slurry formed is within an appropriate range. Therefore, the particles constituting the negative electrode slurry are smoothly dispersed. In addition, when the value of the size of the silicon-based active material is equal to or greater than the lower limit of the range, the contact area between the silicon particles and the conductive material is excellent due to the presence of a composite composed of a conductive material and a binder in the negative electrode slurry, thereby increasing the possibility of a continuous conductive network, thereby increasing the capacity retention rate. Note that when the average particle size satisfies the above range, excessively large silicon particles are excluded, thereby forming a smooth negative electrode surface. Therefore, the current density non-uniformity during charge and discharge can be prevented.
[0111] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.1 m 2 / g to 150.0 m 2 / g, more preferably 0.1 m 2 / g to 100.0m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, and most preferably 0.2 m 2 / g to 18.0 m 2 / g. The BET specific surface area is measured according to DIN 66131 (using nitrogen).
[0112] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a silicon-containing film or coating.
[0113] In an exemplary embodiment of the present application, the content of the silicon-based active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.
[0114] In another exemplary embodiment, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0115] The negative electrode active material layer composition according to the present application uses a specific conductive material and a binder that can control the volume expansion rate during charging and discharging even when a silicon-based active material with a significantly high capacity within the above range is used, and provides a pattern portion that satisfies the range of Formula 1 above, so that the output characteristics during charging and discharging are excellent without reducing the performance of the negative electrode.
[0116] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical shape, and the sphericity (circularity) thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0117] In the present application, circularity is determined by the following formula 1-1, where A is an area and P is a boundary line.
[0118] [Formula 1-1]
[0119] 4πA / P 2
[0120] In the related art, only graphite compounds are usually used as negative electrode active materials. However, in recent years, with the increasing demand for high-capacity batteries, attempts to mix and use silicon-based compounds have increased in order to increase capacity. However, in the case of silicon-based compounds, even when the properties of the silicon-based active material itself are adjusted as described above according to the present application, its volume may expand rapidly during the charge and discharge process, causing some problems that may destroy the conductive path formed in the negative electrode active material layer.
[0121] Therefore, in an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a planar conductive material, and a line-shaped conductive material.
[0122] In an exemplary embodiment of the present application, the point-shaped conductive material refers to a point-shaped or spherical conductive material that can be used to improve the conductivity of the negative electrode and has conductivity without causing chemical changes. Specifically, the point-shaped conductive material can be one or more substances selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and preferably can contain carbon black in terms of high conductivity and excellent dispersibility.
[0123] In an exemplary embodiment of the present application, the BET specific surface area of the dot-shaped conductive material may be 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m2 / g or less, more preferably 50 m 2 / g and above 60 m 2 / g or less.
[0124] In an exemplary embodiment of the present application, the content of the functional group (volatile substance) of the dot-shaped conductive material may satisfy the range of 0.01% to 1%, preferably 0.01% to 0.3%, and more preferably 0.01% to 0.1%.
[0125] In particular, when the content of the functional group of the dot-shaped conductive material satisfies the above range, the functional group exists on the surface of the dot-shaped conductive material, so that when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, in the present invention, since silicon particles and a specific binder are used, the content of the functional group of the dot-shaped conductive material can be reduced, which shows an excellent effect on improving dispersibility.
[0126] In an exemplary embodiment of the present application, a dot-shaped conductive material having a functional group content within the above range is included together with a silicon-based active material, and the content of the functional group may be adjusted according to a degree of heat treatment of the dot-shaped conductive material.
[0127] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0128] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material.
[0129] The planar conductive material improves conductivity by increasing the surface contact between silicon particles in the negative electrode, and can be used to suppress the disconnection of the conductive path due to volume expansion. The planar conductive material can be expressed as a plate-like conductive material or a bulk conductive material.
[0130] In an exemplary embodiment of the present application, the planar conductive material may be provided in a form bonded to the surface of the silicon-based particles. Specifically, the planar conductive material may be provided in a form such that -OH groups or -O on the surface of the silicon-based particles are bonded to the hydrophilic groups of the planar conductive material.
[0131] In an exemplary embodiment of the present application, the planar conductive material may include one or more selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.
[0132] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 3.5 μm to 5 μm. When the above range is met, sufficient particle size leads to easy dispersion without causing excessive increase in viscosity of the negative electrode slurry. Therefore, when the same equipment and time are used for dispersion, the dispersion effect is excellent.
[0133] In an exemplary embodiment of the present application, the planar conductive material may have D10 of 0.5 μm to 2.0 μm, D50 of 2.5 μm to 3.5 μm, and D90 of 6.5 μm to 15.0 μm.
[0134] In an exemplary embodiment of the present application, as for the planar conductive material, a high specific surface area planar conductive material or a low specific surface area planar conductive material having a high BET specific surface area may be used.
[0135] In an exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used but is not limited to. However, in particular, the planar conductive material according to the present application may be affected to a certain extent by the dispersion effect in terms of electrode performance, so it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause dispersion problems.
[0136] In an exemplary embodiment of the present application, the BET specific surface area of the planar conductive material may be 1 m 2 / g or above.
[0137] In another exemplary embodiment, the BET specific surface area of the planar conductive material may be 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m 2 / g or less.
[0138] For the planar conductive material of the present application, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used.
[0139] In another exemplary embodiment, the planar conductive material is a high specific surface area planar conductive material, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m2 / g or less, more preferably 100 m 2 / g and above 300 m 2 / g or less.
[0140] In another exemplary embodiment, the planar conductive material is a low specific surface area planar conductive material, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g or more and 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.
[0141] Other conductive materials may include linear conductive materials, such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may contain a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term 'bundle-type' herein refers to a bundle-like or rope-like secondary shape, in which a plurality of carbon nanotube units are arranged side by side or wound in a manner in which the longitudinal axes of the carbon nanotube units are substantially oriented in the same direction. The carbon nanotube unit has a cylindrical graphite sheet with a nanometer-scale diameter and has an sp2 bonding structure. In this case, depending on the curling angle and structure of the graphite sheet, the characteristics of a conductor or a semiconductor may be exhibited. Compared with wound-type carbon nanotubes, bundle-type carbon nanotubes may be more evenly dispersed during the manufacture of the negative electrode, and may more smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.
[0142] As an example, the linear conductive material can be a single-walled carbon nanotube (SWCNT) having a large BET specific surface area, a linear form, a very small diameter and a very long length. Wire-shaped conductive materials such as SWCNT cannot be stretched by dispersion and have a strong ability to recover their original form when dried. As a result, wire-shaped conductive materials such as SWCNT have a strong ability to recover their original form when dried, so it is usually present in the form of wrapping or connecting the negative electrode active material or the secondary agglomerate. The bonding method can be adsorption by van der Waals forces.
[0143] In an exemplary embodiment of the present application, the content of the negative electrode conductive material may be 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.
[0144] In another exemplary embodiment, the content of the negative electrode conductive material may be 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 10 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0145] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material and a linear conductive material.
[0146] In an exemplary embodiment of the present application, the negative electrode conductive material may include 80 parts by weight or more and 99.9 parts by weight or less of a planar conductive material and 0.1 parts by weight or more and 20 parts by weight or less of a linear conductive material based on 100 parts by weight of the negative electrode conductive material.
[0147] In another exemplary embodiment, the negative electrode conductive material may include 80 parts by weight or more and 99.9 parts by weight or less, preferably 85 parts by weight or more and 99.9 parts by weight or less, and more preferably 95 parts by weight or more and 98 parts by weight or less of the planar conductive material, based on 100 parts by weight of the negative electrode conductive material.
[0148] In another exemplary embodiment, the negative electrode conductive material may include 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.1 parts by weight or more and 15 parts by weight or less, and more preferably 2 parts by weight or more and 5 parts by weight or less of the linear conductive material, based on 100 parts by weight of the negative electrode conductive material.
[0149] In an exemplary embodiment of the present application, the negative electrode conductive material comprises a planar conductive material and a linear conductive material and satisfies the above-mentioned composition and proportion respectively, so that the life characteristics of the existing lithium secondary battery are not significantly affected. In particular, when the planar conductive material and the linear conductive material are included, the number of chargeable and dischargeable sites is increased, so that the output characteristics at a high C rate are excellent, and the amount of gas generated at high temperature is reduced.
[0150] The negative electrode conductive material according to the present application has a configuration completely different from that of the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application is used to maintain contact between the silicon-based active material whose electrode volume expands greatly due to charge and discharge, while the positive electrode conductive material is used to impart a certain conductivity and act as a buffer during rolling, and is completely different from the negative electrode conductive material of the present invention in terms of configuration and function.
[0151] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different configuration from the conductive material applied to the graphite-based active material. That is, since the conductive material used for the electrode with the graphite-based active material has only particles smaller than the active material, the conductive material has the characteristics of improving output characteristics and imparting a certain conductivity, and is completely different from the negative electrode conductive material applied together with the silicon-based active material in the present invention in terms of configuration and function.
[0152] In an exemplary embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and function different from that of the carbon-based active material commonly used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material processed into a spherical or dot-like shape for use in order to promote the storage and release of lithium ions.
[0153] On the other hand, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the planar conductive material is a material contained in the negative electrode active material layer in order to maintain a conductive path, and means a material for ensuring a conductive path in a planar shape inside the negative electrode active material layer rather than playing a role in storing and releasing lithium.
[0154] That is, in the present application, using plate-like graphite as a conductive material means processing graphite into a planar or plate-like shape and using it as a material for ensuring a conductive path rather than for storing or releasing lithium. In this case, the negative electrode active material contained together has a large capacity characteristic in terms of storing and releasing lithium, and is used to store and release all lithium ions transferred from the positive electrode.
[0155] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.
[0156] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.
[0157] The negative electrode binder according to an exemplary embodiment of the present application is used to retain the silicon-based active material and the negative electrode conductive material to prevent the negative electrode structure from being distorted and deformed when the volume of the silicon-based active material expands and relaxes. When these effects are met, all general negative electrode binders can be applied. Specifically, an aqueous binder can be used, and more specifically, a PAM-based binder can be used.
[0158] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and 5 parts by weight or more, 10 parts by weight or more, based on 100 parts by weight of the negative electrode active material layer composition.
[0159] Compared with the existing carbon-based negative electrode, when the Si-based negative electrode is used, the aqueous binder is applied in the above weight portion, so that a dot-shaped conductive material with a low functional group content can be used. In addition, the above characteristics make the dot-shaped conductive material hydrophobic and have excellent bonding strength between the conductive material / binder.
[0160] In an exemplary embodiment of the present application, a negative electrode slurry including a negative electrode active material layer composition may be coated on one surface or both surfaces of a negative electrode collector to form a negative electrode for a lithium secondary battery.
[0161] In an exemplary embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry including a negative electrode composition to one surface or both surfaces of a negative electrode collector layer and drying.
[0162] In an exemplary embodiment of the present application, the negative electrode slurry may include a negative electrode active material layer composition and a slurry solvent.
[0163] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy a range of 5% or more and 40% or less.
[0164] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.
[0165] The solid content of the negative electrode slurry may mean the content of the negative electrode active material layer composition contained in the negative electrode slurry, and may mean the content of the negative electrode active material layer composition based on 100 parts by weight of the negative electrode slurry.
[0166] When the solid content of the negative electrode slurry satisfies the above range, during the formation of the negative electrode active material layer, the viscosity is appropriate, thereby minimizing the aggregation of particles of the negative electrode composition, thereby effectively forming the negative electrode active material layer.
[0167] In an exemplary embodiment of the present application, the slurry solvent may be used without limitation as long as it can disperse the above-mentioned negative electrode composition, and specifically, water or NMP may be used.
[0168] Figure 11 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, a negative electrode 100 for a lithium secondary battery including a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10 can be seen. Figure 1 It is shown that the negative electrode active material layer is formed on one surface of the negative electrode collector layer, but the negative electrode active material layer may be formed on both surfaces of the negative electrode collector layer.
[0169] In an exemplary embodiment of the present application, the thickness of the negative electrode collector layer is generally 1 μm to 100 μm. There is no particular limitation on this negative electrode collector layer, as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, microscopic concave-convex can be formed on the surface of the negative electrode collector layer to enhance the binding force of the negative electrode active material, and can be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam or a non-woven fabric.
[0170] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.
[0171] However, the thickness may be variously modified depending on the type and purpose of the negative electrode used, and is not limited thereto.
[0172] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.
[0173] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy the range of 10% to 60% both inclusive, preferably 20% to 50% both inclusive, and more preferably 30% to 45% both inclusive.
[0174] The porosity varies depending on the composition and content of the silicon-based active material, conductive material and binder contained in the negative electrode active material layer. In particular, when the silicon-based active material and conductive material according to the present application are contained in a specific composition and content, the above range is satisfied, so that the electrode has conductivity and resistance within an appropriate range.
[0175] An exemplary embodiment of the present application provides a lithium secondary battery including a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
[0176] Figure 21 is a diagram showing a stacking structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, a negative electrode 100 for a lithium secondary battery including a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10 is shown, a positive electrode 200 for a lithium secondary battery including a positive electrode active material layer 40 on one surface of a positive electrode collector layer 50 is shown, and the negative electrode 100 for a lithium secondary battery and the positive electrode 200 for a lithium secondary battery are formed into a stacking structure with a separator 30 interposed therebetween.
[0177] A secondary battery according to an exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for lithium secondary batteries. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described above, its detailed description is omitted.
[0178] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.
[0179] In the positive electrode, there is no particular restriction on the positive electrode collector, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., etc. can be used. In addition, the thickness of the positive electrode collector can generally be 3 μm to 500 μm, and the surface of the collector can be formed with microscopic concave-convex to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0180] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or a compound substituted by one or more transition metals; lithium iron oxide such as LiFe3O4; lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5 and Cu2V2O7; Ni-site lithium nickel oxide, composed of the chemical formula LiNi 1-c2 M c2 O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.6); lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3O2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.6) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4, wherein a portion of Li in the chemical formula is replaced by an alkaline earth metal ion, etc., but is not limited thereto. The positive electrode may be Li metal.
[0181] In an exemplary embodiment of the present application, the positive electrode active material includes a lithium composite transition metal compound containing nickel (Ni), cobalt (Co) and manganese (Mn), the lithium composite transition metal compound includes a single particle or a secondary particle, and the average particle size (D50) of the single particle may be 1 μm or more.
[0182] For example, the average particle size (D50) of a single particle may be 1 μm to 12 μm, 1 μm to 8 μm, 1 μm to 6 μm, greater than 1 μm to 12 μm, greater than 1 μm to 8 μm, or greater than 1 μm to 6 μm.
[0183] Even when the formed single particles have a small average particle size (D50) of 1 μm or more and 12 μm or less, the particle strength may be excellent. 2 The particle strength of a single particle can be 100 to 300 MPa when rolled at 650 kgf / cm 2 The strong rolling pressure on a single particle also reduces the increase in particles in the electrode due to particle breakage, thereby improving the battery life characteristics.
[0184] The single particle can be produced by mixing and firing a transition metal precursor and a lithium source material. The secondary particle can be produced by a different method from the single particle, and its composition can be the same as or different from that of the single particle.
[0185] The method of forming the single particles is not particularly limited, but may generally be formed by overfiring at an elevated firing temperature, or may be produced by using an additive such as a grain growth promoter that assists overfiring or by changing a starting material.
[0186] For example, firing is performed at a temperature at which a single particle can be formed. For this purpose, firing should be performed at a temperature higher than the temperature during the manufacture of secondary particles. For example, when the composition of the precursor is the same, firing should be performed at a temperature about 30°C to 100°C higher than the temperature during the manufacture of secondary particles. The firing temperature for forming a single particle can vary according to the metal composition in the precursor. For example, when a single particle is formed with a high Ni NCM lithium composite transition metal oxide having a nickel (Ni) content of 80 mol % or more, the firing temperature can be about 700°C to 1000°C, preferably about 800°C to 950°C. When the firing temperature satisfies the above range, a positive active material containing a single particle having excellent electrochemical properties can be manufactured. If the firing temperature is lower than 790°C, a positive active material containing a lithium composite transition metal compound in the form of a secondary particle can be manufactured. If the firing temperature exceeds 950°C, over-firing will occur, and a layered crystal structure cannot be properly formed, which may deteriorate the electrochemical performance.
[0187] In this specification, a single particle is a term used to distinguish from typical secondary particles formed by agglomeration of tens to hundreds of primary particles, and is a concept that includes a single particle composed of one primary particle and a quasi-single particle form that is an agglomerate of 30 or less primary particles.
[0188] Specifically, in the present invention, the single particle may be a single particle composed of one primary particle or a quasi-single particle form which is an agglomerate of 30 or less primary particles, and the secondary particle may be an agglomerate form of several hundred primary particles.
[0189] In the exemplary embodiment of the present application, the lithium composite transition metal compound as the positive electrode active material further includes secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.
[0190] In the present invention, the single particle may be a single particle composed of one primary particle or a quasi-single particle form which is an agglomerate of 30 or less primary particles, and the secondary particle may be an agglomerate of several hundred primary particles.
[0191] The lithium composite transition metal compound may further include secondary particles. The secondary particles refer to a form formed by agglomeration of primary particles and can be distinguished from the concept of single particles including one primary particle, one single particle, and a quasi-single particle form that is an agglomeration of 30 or less primary particles.
[0192] The particle size (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles may be 0.05 m2 / g to 10 m 2 / g, preferably 0.1 m 2 / g to 1 m 2 / g, more preferably 0.3m 2 / g to 0.8 m 2 / g.
[0193] In another exemplary embodiment of the present application, the secondary particles are agglomerates of primary particles, and the average particle size (D50) of the primary particles is 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of agglomerates of hundreds of primary particles, and the average particle size (D50) of the primary particles may be 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.
[0194] When the average particle size (D50) of the primary particles satisfies the above range, a single particle positive electrode active material with excellent electrochemical performance can be formed. If the average particle size (D50) of the primary particles is too small, the number of agglomerates of the primary particles forming the lithium nickel oxide particles increases, thereby reducing the inhibitory effect on particle breakage during rolling. If the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles may be extended, thereby increasing resistance and reducing output characteristics.
[0195] According to another exemplary embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles. As a result, even if the particle size of the formed single particles is small, they can have excellent particle strength, thereby reducing the phenomenon of increasing particles in the electrode due to particle breakage, thereby improving the life characteristics of the battery.
[0196] In an exemplary embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.
[0197] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm, 1.5 μm to 15 μm, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.
[0198] When the average particle size (D50) of a single particle is smaller than the average particle size (D50) of a secondary particle, for example, when the above range is met, even if the particle size of the formed single particles is small, they can have excellent particle strength, resulting in the reduction of the increase in microparticles in the electrode due to particle breakage, thereby improving the battery life characteristics and energy density.
[0199] According to another exemplary embodiment of the present application, the content of the single particle is 15 to 100 parts by weight based on 100 parts by weight of the positive electrode active material. The content of the single particle may be 20 to 100 parts by weight or 30 to 100 parts by weight based on 100 parts by weight of the positive electrode active material.
[0200] For example, based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 100 parts by weight or less.
[0201] When a single particle within the above range is included, excellent battery characteristics can be exhibited when combined with the above negative electrode material. In particular, when the content of the single particle is 15 parts by weight or more, the phenomenon of increasing fine particles in the electrode due to particle rupture can be reduced during the rolling process after manufacturing the electrode, thereby improving the life characteristics of the battery.
[0202] In an exemplary embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the content of the secondary particles may be 85 parts by weight or less based on 100 parts by weight of the positive electrode active material. Based on 100 parts by weight of the positive electrode active material, the content of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less. Based on 100 parts by weight of the positive electrode active material, the content of the secondary particles may be 0 parts by weight or more.
[0203] When the above range is met, the above effect caused by the presence of a single particle in the positive electrode active material can be maximized. In the case of a positive electrode active material containing secondary particles, its composition may be the same as or different from those exemplified in the above single particle positive electrode active material, and may refer to the form of an agglomerate of a single particle.
[0204] In an exemplary embodiment of the present application, in 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material can be more than 80 parts by weight and less than 99.9 parts by weight, preferably more than 90 parts by weight and less than 99.9 parts by weight, more preferably more than 95 parts by weight and less than 99.9 parts by weight, and most preferably more than 98 parts by weight and less than 99.9 parts by weight.
[0205] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material described above.
[0206] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the constituted battery. Specific examples may include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and any one thereof or a mixture of two or more thereof may be used.
[0207] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-to-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, etc., and any one thereof or a mixture of two or more thereof may be used.
[0208] The separator is used to separate the negative electrode and the positive electrode and provide a lithium ion migration path, wherein any separator can be used as the separator without particular limitation, as long as it is commonly used in secondary batteries, in particular, it is preferred to use a separator having high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, ordinary porous nonwoven fabrics can be used, for example, nonwoven fabrics formed by high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator with a monolayer or multilayer structure can be selectively used.
[0209] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that can be used to manufacture a lithium secondary battery, but are not limited thereto.
[0210] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0211] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.
[0212] Especially, in carbonate system organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents and they have high dielectric constant, thereby can dissociate lithium salt well, therefore can preferably use.When cyclic carbonate and linear carbonate with low viscosity and low dielectric constant such as dimethyl carbonate and diethyl carbonate are mixed with use in suitable ratio, can prepare electrolyte with high conductivity, therefore may more preferably use.
[0213] A lithium salt may be used as the metal salt, and the lithium salt is a material that is easily dissolved in a non-aqueous electrolyte, wherein, for example, one or more substances selected from the group consisting of the following may be used as anions of the lithium salt: - , Cl - ,I - 、NO3 - 、N(CN) 2- 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN -and (CF3CF2SO2)2N - .
[0214] In order to improve the life characteristics of the battery, inhibit the decline of the battery capacity, improve the discharge capacity of the battery, etc., in addition to the above-mentioned electrolyte components, the electrolyte may also contain one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.
[0215] An exemplary embodiment of the present invention provides a battery module including a secondary battery as a unit battery and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries having high capacity, high rate capability, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0216] Preferred embodiments will be provided below to better understand the present invention. It will be apparent to those skilled in the art that the embodiments are provided only to illustrate the present invention, and various modifications and changes can be made within the scope and technical spirit of the present invention. Such modifications and changes naturally fall within the scope of the claims contained herein.
[0217] Invention method
[0218] <Preparation Example>
[0219] <Preparation of negative electrode>
[0220] Si (average particle size (D50): 3.5 μm) used as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide used as a binder were added to distilled water used as a negative electrode slurry forming solvent in a weight ratio of 80:10:0.4:9.6 to prepare a negative electrode slurry (solid concentration: 25 wt %).
[0221] The first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is SWCNT.
[0222] As a mixing method, after the first conductive material, the second conductive material, the binder and water were dispersed with a homomixer at 2500 rpm for 30 minutes, the active material was added to the dispersion and then dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0223] The negative electrode slurry was prepared at 85 mg / 25 cm 2 A loading amount of was coated on both surfaces of a copper collector (thickness: 8 μm) used as a negative electrode collector, and then roll-pressed and dried in a vacuum oven at 130°C for 10 hours to form a negative electrode active material layer, thereby preparing a negative electrode (porosity of the negative electrode: 40.0%).
[0224] Thereafter, a pattern was formed in the negative electrode active material layer using a laser, and the shape of the pattern and its information are shown in the following Table 1. In this case, the same total volume (A+B) of the negative electrode active material layer was formed, and the experiment was performed by changing only the volume of the pattern portion.
[0225]
[0226] In Table 1, Comparative Example 1 corresponds to the case where a negative electrode for a secondary battery was manufactured in the same manner as above, but without patterning.
[0227] Experimental Example 1. Evaluation of initial discharge capacity
[0228] For the secondary batteries including the negative electrodes prepared in the examples and comparative examples, the first discharge capacity was measured at 4.2-3.0 V 0.33 C / 0.33 C using an electrochemical charge and discharge device.
[0229] Experimental Example 2. Evaluation of the life characteristics of a single cell at room temperature
[0230] For the secondary batteries including the negative electrodes prepared in the examples and comparative examples, the life span and capacity retention rate were evaluated using an electrochemical charge and discharge device. The secondary batteries were cycled at 4.2-3.0 V 1 C / 0.5 C, and the number of cycles when the capacity retention rate reached 80% was measured.
[0231] Capacity retention rate (%) = {(discharge capacity of the Nth cycle) / (discharge capacity of the first cycle)}×100
[0232] Experimental Example 3. Evaluation of resistance increase rate measurement
[0233] During the test in Experimental Example 2, after measuring the capacity retention rate by charging and discharging the secondary battery at 0.33 C / 0.33 C (4.2-3.0 V) every 50 cycles, the resistance was measured by discharging the secondary battery at 2.5 C pulse at SOC50, and the resistance increase rate was compared and analyzed.
[0234] For the evaluation of the resistance increase rate measurement, data at 150 cycles were calculated respectively.
[0235] Experimental Example 4. Evaluation of battery swelling
[0236] For the battery evaluated in Experimental Example 2, after formation in a state of 150-cycle discharge (3.0 V), the total thickness increase rate of the battery was calculated.
[0237] Experimental Example 5. Evaluation of hole resistance
[0238] A coin-symmetric cell was prepared using the negative electrodes prepared in the examples and comparative examples, and the pore resistance was calculated by measuring the impedance from 300 kHz to 300 mHz by EIS at 25°C.
[0239] The evaluation results of Experimental Examples 1 to 5 are shown in Table 2 below.
[0240]
[0241] The negative electrode for the lithium secondary battery of the present invention includes a silicon-based active material, and its goal is high capacity and high energy density. In this case, the silicon-based active material is high in the negative electrode active material layer, and therefore, volume expansion during charge and discharge may cause problems. In the case of the negative electrode of Examples 1 to 4, the negative electrode active material layer includes a pattern portion, and in particular, it can be confirmed that the volume of the pattern portion and the negative electrode active material layer satisfies the relationship of Formula 1 above.
[0242] Accordingly, it can be confirmed that the negative electrode comprising a negative electrode active material layer satisfying the above formula 1 can maximize the life characteristics of the lithium secondary battery by reducing the volume expansion during charge and discharge, and can provide a lithium secondary battery having the advantages of a silicon-based negative electrode, namely high density and high capacity characteristics, while having excellent fast charging performance.
[0243] Comparative Example 1 is a negative electrode that does not include a pattern portion, and the life characteristics are deteriorated as shown in Experimental Example 2, the resistance increase rate is high as shown in Experimental Example 3, and the battery expansion is high as shown in Experimental Example 4. This is because no pattern portion that can prevent and relax the volume expansion of the silicon-based active material (especially pure Si) is formed, and it can be confirmed that the life characteristics are rapidly deteriorated.
[0244] Comparative Example 2 corresponds to the case where the negative electrode active material layer has a pattern portion as in the present invention, but the range is smaller than the range of Formula 1, that is, the volume of the pattern portion is smaller than the volume set in the present application. In this case, the same results as those of Comparative Example 1 can also be shown. That is, it can be confirmed that when the volume of the pattern portion is smaller than the set volume, the life characteristics deteriorate to the same extent as when the pattern portion is not formed.
[0245] Comparative Example 3 corresponds to the case where the volume of the pattern portion is larger than the volume set in the present application (ie, when it exceeds the range of Formula 1). In this case, it can be confirmed that the life characteristics are similar to those of the embodiments of the present application. However, it can be confirmed that the desired capacity cannot be achieved in Experimental Example 1 because the pattern portion is over-ensured in order to control volume expansion. That is, pure Si having better capacity characteristics than carbon-based active materials is used to ensure capacity characteristics and fast charging, however, it can be confirmed that when the pattern portion is over-formed to ensure only the life characteristics, the capacity characteristics are deteriorated instead, and the corresponding negative electrode cannot be used as a negative electrode.
[0246] In summary, when the range of the above formula 1 is satisfied, not only the volume expansion of the stacked pouch battery can be controlled, but also the volume expansion of the cylindrical and square batteries rolled into a roll can be controlled, thereby producing a favorable effect on high energy density and high capacity characteristics. In addition, it can be confirmed through experimental examples that even when the formation charging speed is increased compared to the existing conditions, there is no difference in volume expansion, and not only the expansion in the x and y directions can be reduced, but also the thickness change in the z direction can be reduced.
Claims
1. A negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a negative electrode current collector layer; and A negative electrode active material layer formed on one surface or both surfaces of the negative electrode current collector layer, The negative electrode active material layer comprises a pattern portion and satisfies the following formula 1: [Formula 1] 5 ≤ [B / (A+B)] × 100(%) ≤ 30 In the above formula 1, A refers to the volume of the negative electrode active material layer excluding the pattern portion, and B refers to the volume of the pattern portion of the negative electrode active material layer.
2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material layer satisfies the following formula 2: [Formula 2] [{(x+x1)(y+y1)(z+z1)-xyz} / xyz] × 100(%) < 50% In the above formula 2, x, y and z are respectively the total width, total length and total thickness of the negative electrode active material layer including the pattern after manufacturing the negative electrode for a lithium secondary battery, and x1, y1, and z1 are length changes in x, y, and z directions, respectively, immediately after the negative electrode for a lithium secondary battery was charged to 4.2 V (0.05C cutoff) with 1 / 3C CC-CV and then discharged to 2.5 V with 1 / 3C CC after manufacturing the negative electrode.
3. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material layer satisfies the following formula 3: [Formula 3] [{(x+x2)(y+y2)(z+z2)-xyz} / xyz] × 100(%) < 100% In the above formula 3, x, y and z are respectively the total width, total length and total thickness of the negative electrode active material layer including the pattern after manufacturing the negative electrode for a lithium secondary battery, and x2, y2 and z2 refer to length changes in x, y and z directions after 300 cycles of charging to 4.2 V (0.05 C cutoff) at 1C CC-CV and discharging to 3.0 V at 0.5C CC after manufacturing the negative electrode for a lithium secondary battery, respectively.
4. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material layer satisfies the following formula 4: [Formula 4] 5 ≤ xyz - {(xi × n)yz + x(yj × m)z - nmxiyjz} ≤ 30 In the above formula 4, x, y and z are respectively the total width, total length and total thickness of the negative electrode active material layer including the pattern after manufacturing the negative electrode for a lithium secondary battery, and n is the number of patterns in the x direction, m is the number of patterns in the y direction, xi refers to the width of the pattern, yj refers to the length of the pattern, i is an integer in the range of 1 to n, and j is an integer in the range of 1 to m. 5 . The negative electrode for a lithium secondary battery according to claim 1 , wherein the pattern portion comprises one or more selected from the group consisting of a 1D pattern, a 2D pattern, a V-shaped pattern, and a U-shaped pattern.
6. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material layer contains a negative electrode active material layer composition, and wherein the negative electrode active material layer composition contains a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.
7. The negative electrode for a lithium secondary battery according to claim 6, wherein the silicon-based active material contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 70 parts by weight or more.
8. The negative electrode for a lithium secondary battery according to claim 6, wherein based on 100 parts by weight of the negative electrode active material layer composition, the content of the silicon-based active material is 60 parts by weight or more.
9. The negative electrode for a lithium secondary battery according to claim 6, wherein the negative electrode conductive material contains a planar conductive material and a linear conductive material, and wherein based on 100 parts by weight of the negative electrode conductive material, the content of the planar conductive material is 80 parts by weight or more and 99.9 parts by weight or less, and the content of the linear conductive material is 0.1 parts by weight or more and 20 parts by weight or less.
10. The negative electrode for a lithium secondary battery according to claim 6, wherein based on 100 parts by weight of the negative electrode active material layer composition, the content of the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less.
11. The negative electrode for a lithium secondary battery according to claim 1, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and wherein the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.
12. A lithium secondary battery, the lithium secondary battery comprising: a positive electrode; the negative electrode for a lithium secondary battery according to any one of claims 1 to 11; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
Citation Information
Patent Citations
Anode for lithium ion battery
JP2009080971A